Speed characteristics of structure motion of the system "athletes-weight" in weightlifters of various gender - Oleshko V.G; Antoniuk O.V (Kharkov National Pedagogical University, 2010)
Speed descriptions of structure of motion of barbell are certain during implementation of competition exercises weightlifters of high qualification of different floor. In researches these implementations of exercises are used 235 strongest weightlifters of the world. It is selected three most informing parameter of motion of barbell. Research receptions are a videocomputer analysis, mathematical statistics. Dependence of these parameters is set on sizes and mass of body of sportsman and floor. All sportsmen with the increase of gravimetric category have gradual growth of rate of climb of motion of barbell only in a jerk in the phase of previous acceleration.